Whitefella culture - Hargrave, Susanne; Summer Institute of Linguistics. Australian Aborigines and Islanders Branch (Darwin : Summer Institute of Linguistics, Australian Aborigines and Islanders Branch, 1991)
Explains white culture "manners" to Aboriginal people in sensitive, easy language.
Keywords: Aboriginal Australians; National characteristics, Australian; Social behaviour; Culture